Improving East/Westbound SDN Connectivity via Enhanced Availability - Santos, Dorabella (2021)
The control plane in software-defined networking (SDN) is composed by a logically centralized set of controllers wihich acts as the brain of the SDN network. These controllers need to be connected through east/westbound interfaces in order to have a synchronized view of the network and therefore it is a key issue to guarantee the intercontroller connectivity for a proper network behaviour. In the present work, the problem of controller placement under QoS constraints with the additional requirement of having the intercontroller connectivity with a given availability at minimum cost is addressed as a bi-objective problem. This problem is NP-complete and to tackle it a heuristic approach is proposed based on the problem decomposition into subproblems. In a previous heuristic to solve a less general problem, a similar strategy was followed based on the assumption that a Steiner tree connecting the controllers is the set of links that should be upgraded to achieve the required availability. In this paper a more general sub-graph is considered for intercontroller availability improvement, and an additional optimization level is also considered to address this more general problem. To assess the performance of the proposed heuristic a baseline heuristic to serve as a benchmark is also proposed. Index Terms—SDN, controller placement, availability, heuris-